Renewable energy deployment - do the benefits outweigh the costs? - Ulrike Lehr; Barbara Breitschopf; Jochen Diekmann; Juri Horst; Marian Klobasa; Frank Sensfuß; Jan Steinbach (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2012)
The increasing use of energy from renewable sources (RE) for the generation of heat and electricity in Germany has also led to an increasingly intensive debate on its advantages and disadvantages. The discussion mostly centers on the cost effects, because beneficial effects often are harder to quantify. Benefits comprise indirect effects or effects which lie far in the future. Scientific studies also frequently focus on single aspects, which cannot be aggregated easily, because they occur in different sectors and comprise technology system-wide effects, distributional effects or overall macro-economic effects. This study intends to answer questions refering to clear definitions of effects when increasing renewable energy, methods of adding and balancing the effects, the choice of methodological approach, support mechanisms, suitable time span or spatial system border. After a brief sketch of the basic methods applied, the contribution will present estimates for a wide range of effects. It closes with suggestions on possibilities how to add and balance the effects.
Keywords: Q4; Q5; 330; renewable energy sources; estimation and evaluation of costs and benefits; distributional; price and macro-economic effects; Erneuerbare Energie; Kosten-Nutzen-Analyse; Deutschland